Consumo e narcisismo nas sociabilidades em rede - Silva, Juliana Correia Almeida e (2014)
In this study 18 sediment samples were collected from the upper continental slope across the coast of the state of Sergipe in January 2007. The composition and distribution pattern of recent foraminifera were studied. For each sample, 300 foraminifera shells were identified, reaching 5400 different specimens. The samples were treated initially with the division by quartering, washed with water, weighed to 1 g and finally screened. The study shows 4504 specimens from benthic and 896 planktonic foraminifera. A total of 167 taxa were identified, with 84 genera and 157 benthic taxa. The benthic species most frequent were Amphistegina sp, Cassidulina laevigata, Siphonina pulchra and Peneroplis carinatus. Benthic and planktonic foraminifera appeared in all samples. For seven genera of planktonic foraminifera, an amount of 10 species could be identified. Planktonic species most frequent were Globigerinoides conglobatus, G. ruber, G. trilobus, Globorotalia menardii e Globigerina bulloides. The 18 sampling sites in the study area are predominantly located in bioclastic environments, except for two points that are located near of the São Francisco canyon, which is a siliciclastic environment. These results are completely new and they will allow extending the composition of foraminifera that occur along the studied area. The data are consistent with those found by other authors in different regions of the northeastern Brazilian coast. Taxonomic changes observed on this study at the generic and specific level of the studied foraminifera agree with literature data.